(untitled) (Research, Society and Development, 2021)
The quality of the watermelon is determined by the total sugars, color, appearance, among others. These, as well as productivity, can be affected by the relationship between source and drain, and it is necessary to study new management techniques for adaptation within the production chain, especially stem pruning. The driving method tutored in mini watermelon is still incipient, however, adaptations are made to the cultivation of melon. Therefore, the goal of this research was to evaluate the pruning and conduction of mini watermelon plants for fruit production. The mini watermelon cultivar Sugar Baby was studied, and the experiment was divided into a plot with type of conduction (low and vertical system) in the plots, and pruning in the subplots (1 or 2 stems), with a randomized block design, with 10 repetitions. It is concluded that the tutored system, low, with one or two stems, gives quality fruits of the mini watermelon ‘Sugar Baby’. In others studies, it is suggested to study in other cultivars, because diferente genetics respond differently, as well as to perform the pruning in nodes diferente from the presente study.